2013
DOI: 10.2174/1874279301004010132
|View full text |Cite
|
Sign up to set email alerts
|

Serum Serotonin Levels are Associated with Antiviral Therapy Outcomes in Patients with Chronic Hepatitis C

Abstract: The role of serotonin in contributing to viral clearance has not been investigated in patients with chronic hepatitis C (HCV). In this prospective study we collected blood samples from 39 patients prior to and during antiviral therapy. Participants completed mood rating scales to monitor psychiatric symptoms, and serum serotonin and tryptophan levels were measured. Significant differences in serotonin levels were found between patients who achieved sustained viral responses (SVRs) and those who did not. Regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
2
4
0
Order By: Relevance
“…Consistent with our previous report [16], we found that in the total sample of patients, serotonin levels were significantly lower after 16 weeks of antiviral therapy, as compared to baseline (week 0) ( t =6.16, df =30, p <.0001). The Low and High Somatic groups did not show significant between-group differences in serotonin levels at week 16.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with our previous report [16], we found that in the total sample of patients, serotonin levels were significantly lower after 16 weeks of antiviral therapy, as compared to baseline (week 0) ( t =6.16, df =30, p <.0001). The Low and High Somatic groups did not show significant between-group differences in serotonin levels at week 16.…”
Section: Resultssupporting
confidence: 92%
“…IFN stimulates indolamine 2,3-dioxygenase (IDO) which leads to a peripheral depletion of tryptophan [15]. Patients on IFN therapy have altered serum levels of tryptophan (a serotonin precursor) and serotonin [16,17], and some of these changes in the serotonergic system are associated with increased depressive symptoms [18,19], as well as with alterations in specific cytokine levels [20]. However, more recent reports including our own findings do not support consistent correlations between IFN-induced depression and serotonin or tryptophan levels [16,2124].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rats had at least 5 days to recover before 25B-NBOMe was administered. The effects of 6-OHDA and 5,7-DHT were confirmed by measuring catecholamine and serotonin levels in brain tissue using high-performance liquid chromatography (Loftis et al, 2010).…”
Section: Methodsmentioning
confidence: 95%
“…Additionally, when we analyzed the diverse cytokine responses, only the levels of IL-17A, IP-10, and FGF among a total of 11 cytokines were significantly associated with RVR in a viral genotype-dependent manner (Table 2 and Fig 1). Baseline levels of several cellular factors such as TSLP [38] and serotonin [39], were also poorly correlated with early virological outcomes upon treatment. Lower IL-17A, FGF, and VEGF levels were differentially measured in the plasma of RVR patients than in that of the non-RVR group when infected with genotype 1.…”
Section: Discussionmentioning
confidence: 99%